ANALYSIS OF INFLUENCE FACTOR OF TECHNOLOGY, SERVICE QUALITY, AND CUSTOMER FOCUS ON CUSTOMER SATISFACTION (Study on Buyer Products of Bandeng Juwana Elrina Semarang) - Y. Sugiarto PH; Ariane Chaterina Natalia Telan (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2011)
This study aims to determine the influence of factor of technology, service quality,andcustomer focus of the customer satisfaction on the Bandeng Juwana Elrina Group Semarang. Andthis research also aims to analyze the most dominant factors that influence on customersatisfaction on the Bandeng Juwana Elrina Group Semarang. The population used in this study isconsumers who ever or frequently come on the Bandeng Juwana Elrina Group Semarang. Thesample in this study are 80 respondents and the techniques used are non-probability samplingtechnique with the approach of accidental sampling (sampling based on chance). From theanalysis result, the indicators in this study are valid and valid variables. And the most dominantfactor that influence on customer satisfaction are factor of technology variables, then the servicequality variable), and the last is the customer focus variable. The dependent variables in this studyare good enough in explaining the independent variable (customer satisfaction). Writer’s advice isBandeng Juwana Elrina Group Semarang need to preserve the good things that have beenassessed by consumers and repair the things that not good enough in consumers sight.Key Words: factor of technology, service quality, customer focus, customer satisfaction